Antidiabetic and Antioxidant Activities of Extract of Entandrophragma Cylindricum (Sprague) Leaves in Male Wistar Rats - Farouk Oladoja; Emmanuel Irokosu; Oluwafemi Kale; Taiwo Olubodun-Obadun (Journal of Research in Applied and Basic Medical Sciences, 2021)
Background & Aims:  Entandrophragma cylindricum (EC) is a tree with a widespread presence in various West African countries. It has wide folkloric use as an anti-sickling, antimalarial, analgesic, anti-inflammatory, and is widely used traditionally in treating diabetes across West Africa. The purpose of this research is to evaluate the antidiabetic potential of the methanolic leaf extract of Entandrophragma cylindricum (EC) in rats. Materials and Methods: Induction of Diabetes mellitus was done by Streptozotocin (STZ) via intraperitoneal route injection. Animals were apportioned into five groups (n=5) for contrasting the activity of EC at three EC doses (25 mg/kg, 50 mg/kg, 150 mg/kg p.o.) against the standard drug (Glibenclamide) and control groups. Rats having elevated glucose levels above 250 mg/dL were considered diabetic and used for the study. Normoglycemic test, Oral Glucose Tolerance Test (OGTT), STZ-Induced diabetes, in-vitro antioxidant properties of EC extract, and in vivo antioxidant property of the serum were assessed. Results: Phytochemistry revealed the presence of tannins, flavonoids, saponins, alkaloids, terpenoids, deoxy-sugars, and anthraquinones. The three doses of EC (150, 50, and 25 mg/kg) used in the study caused a significant decrease in blood glucose levels in the STZ-induced diabetic rat model. Also, EC (150, 50, and 25 mg/kg) produced a significant (p< 0.001) increase respectively in the body weight from day 0 to day 30 when compared with the untreated diabetic rat. Our results indicated that EC might be a potent free radical scavenger, as it scavenged the 2,2 -diphenyl picrylhydrazyl (DPPH) radical, hydroxyl radical, and NO radicals in vitro. EC also showed a significant anti-lipid peroxidative effect in vivo. Histologic analysis revealed the regenerative impact of EC on the β-cells of diabetic rats. Conclusion: Findings revealed that EC possess antihyperglycemic and antioxidant effects.